Pushing the KIT 2 MW Coaxial-Cavity Short-Pulse Gyrotron Towards a DEMO Relevant Design - Ruess, Sebastian (Karlsruher Forschungsberichte aus dem Institut fur Hochleistungsimpuls- und Mikrowellentechnik series, 2021)
Magnetic fusion is one approach to generate thermonuclear fusion power in an environmental friendly way. The Electron Cyclotron Resonance Heating is considered as the major concept for startup, heating and control of the fusion plasma. Megawatt-class gyrotrons generate the required microwave power. This work focuses on advanced key components and technologies for a DEMO relevant 2 MW gyrotron. One major focus is on the development of advanced Magnetron Injection Guns. Another focus is on the red.